Performance Evaluation of Different Types of CMOS Operational Transconductance (International Journal of Engineering and Computer Science, 2014)
The Operational Transconductance Amplifier is a basic building blocks found in many analog circuits such as data converter’s (ADC& DAC) and Gm-c filters. The OTA is an amplifier whose differential input voltage produces an output current .Thus ,it is a voltage controlled current source(VCCS) whereas the Op-amp are voltage controlled voltage source(VCVS). There is usually an additional input for a current to control the amplifier’s transconductance. The paper represents the different topology of CMOS OTA is described and at last comparison between different configuration is given.